Peer‐supported lifestyle interventions on body weight, energy intake, and physical activity in adults: A systematic review and meta‐analysis. (13th August 2021) - Lim, Siew; Lee, Wai Kit; Tan, Andy; Chen, Mingling; Tay, Chau Thien; Sood, Surbhi; Pirotta, Stephanie; Moran, Lisa J.; Daivadanam, Meena; Busija, Ljoudmila; Skouteris, Helen; Awoke, Mamaru A.; et al.
Summary: There is an increasing interest in peer interventions in the management of chronic conditions, but evidence on peer interventions for body weight is lacking. The aim of this study was to examine the efficacy of peer interventions on body weight, energy intake, and physical activity in adults. Interventions delivered by peer (lay member that participants identify with) were included. We searched 14 databases. Outcomes were combined in the meta‐analysis using the inverse variance random‐effects model. From 2435 articles, 65 articles were included in the systematic review and meta‐analysis ( n = 15, 673). Peer interventions resulted in significant reduction in weight (mean difference [MD] −1.05 kg; 95% confidence interval [CI] −1.68, −0.43; 95% prediction interval [PI] −3.25, 1.14; 28 studies; 7142 participants), BMI (MD −0.24 kg/m 2 ; 95% CI −0.44, −0.04; 95% PI −0.92, 0.45; 25 studies; 6672 participants), waist circumference (MD −0.75 cm; 95% CI −1.29, −0.21; 95% PI −1.36, −0.14; 12 studies; 4280 participants), and significant increase in physical activity (SMD 0.20; 95% CI 0.09, 0.32; 95% PI −0.46, 0.86; 41 studies; 10, 778 participants) with no significant effect on energy intake. This study suggests peer interventions are effective in reducing waist circumference, but further research is needed to confirm its effect on other obesity‐related outcomes.